Book Review: Cooper, E. and Pratten, D., editors. 2015: Ethnographies of Uncertainty in Africa. (October 2018) - Groenewoudt, Aleid
Cooper, E. and Pratten, D., editors. 2015: Ethnographies of Uncertainty in Africa . Anthropology, Change and Development Series . UK: Palgrave Macmillan. xiii + 198 p. Ä89, 99 (Paperback). Ä93, 99. ISBN: 978-1-137-35082-4 (Hardback). ISBN: 978-1-349-46860-7 (Softcover).